Magnetic manganese dioxide tunable electromagnetic wave absorbing material and preparation method thereof
The cage-shaped manganese dioxide nanowire/multi-layer expanded graphite carbon-based composite material is prepared by microwave hydrothermal-flash oxidation method, which solves the problem of complex and poor preparation processes of existing electromagnetic wave absorption and shielding materials, and realizes the tunable dual-effect function and performance of the material.
Patent Information
- Application Number
- CN202411775056.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The preparation process of existing electromagnetic wave absorption and shielding materials is complex and the shielding effect is poor, making it difficult to simultaneously regulate electromagnetic wave absorption and shielding performance.
Cage-shaped manganese dioxide nanowires/multi-layer expanded graphite carbon-based composite materials are prepared by microwave hydrothermal-frequency oxidation method. The manganese oxide nanowires are grown in situ by microwave-assisted hydrothermal, and the composition is controlled by flash heating oxidation, so as to achieve the dual-effect function of electromagnetic wave absorption and shielding.
The tunable phase and electromagnetic absorption shielding performance of manganese dioxide nanowire/carbon material composite material is achieved, and the problems of complicated steps, time-consuming and low efficiency of traditional process are overcome, and materials with excellent electromagnetic wave absorption and shielding performance are prepared.
Smart Images

Figure CN119551726A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new material synthesis and preparation, and in particular to a magnetic manganese dioxide tunable electromagnetic wave absorbing material and a preparation method thereof. Background Art
[0002] With the development of wireless communication technology, the use of electromagnetic waves has increased, affecting the safety of electronic equipment and human body. Therefore, the demand for high-performance electromagnetic wave absorption and shielding materials has increased, becoming a research hotspot in many fields. However, traditional absorbing / shielding materials usually use conductors such as graphene, MXene, carbon nanotubes and semiconductors such as transition metal sulfides and oxides to increase dielectric loss; or use the resonance and spatial matching characteristics of magnetic materials to increase magnetic loss. Both strategies are to regulate the absorption or shielding performance of composite materials for electromagnetic waves alone, and fail to simultaneously regulate to obtain materials with excellent electromagnetic wave absorption and shielding performance.
[0003] CN202411156855 discloses a preparation method and application of a core-sheath structured FeNi@(Co / CN)@ carbon fiber composite absorbing material. The method comprises mixing a mixed solution of polyacrylonitrile and ZIF-67 powder as an external phase solution, mixing Fe powder and Ni powder as an internal phase solution, adopting a coaxial electrospinning process to manufacture coaxial fibers, and finally carbonizing the fibers in a reducing atmosphere to obtain a core-sheath structured FeNi@(Co / CN)@ carbon fiber. The prepared absorbing material has a minimum reflection loss (RL min ) is -61.84dB, and when the matching thickness is 2.37mm, the effective absorption bandwidth (EAB) is 6.24GHz, but the operation is difficult and the matching thickness is large. CN202410650229 discloses a carbon-based composite material for electromagnetic shielding and a preparation method thereof, specifically, carbonized nanocellulose is used as a matrix to load Fe3O4 magnetic nanoparticles, and is prepared by freeze-drying integrated casting, subsequent high-temperature heat treatment and coating treatment. The composite material has a total shielding effectiveness of more than 75dB in the range of 8 to 12GHz, and a reflectivity of less than 0.06, but the related process is time-consuming, the steps are complicated, the reaction conditions are harsh, the shielding band is narrow and the efficiency is low.
[0004] Therefore, it is crucial to develop a simple, efficient, and tunable electromagnetic wave absorbing and shielding composite material and its preparation method, which can meet the needs of mass production of high-quality and high-performance electromagnetic wave absorbing and shielding composite materials. Summary of the invention
[0005] The purpose of the present invention is to provide a magnetic manganese dioxide tunable electromagnetic wave absorbing material and a preparation method thereof, so as to solve the problems that the preparation process of existing composite materials with electromagnetic wave absorption and shielding performance is complicated and the shielding effect is poor.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: a magnetic manganese dioxide tunable electromagnetic wave absorbing material and a preparation method thereof, characterized in that the preparation method comprises the following steps: a magnetic manganese dioxide tunable electromagnetic wave absorbing material and a preparation method thereof, characterized in that the preparation method comprises the following steps:
[0007] S1. Weigh KMnO4, a reducing agent and potassium salt in turn and add them to a beaker filled with deionized water, stir until mixed, and obtain material a;
[0008] S2. Weigh the carbon material, add it to material a, stir and mix thoroughly to obtain material b;
[0009] S3. Place material b in a Teflon crucible and use microwave-assisted hydrothermal in-situ growth of manganese oxide nanowires. After the reaction is completed, rinse with deionized water to remove K + ions, washed and filtered, and then dried to obtain material c, i.e., a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material precursor;
[0010] S4. Place material c in a quartz crucible, perform flash heating oxidation in a microwave tube furnace, and deeply oxidize the material on its surface that has not been completely converted into manganese oxide to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material.
[0011] A further technical solution is that the carbon material in step S2 is one or more of expanded graphite, carbon fiber, carbon nanotube, and carbon black.
[0012] A further technical solution is that in step S1, the reducing agent is one of urea and hydrazine hydrate, and the potassium salt is one of KCl, KNO3, and K2SO4.
[0013] A further technical solution is that the mass ratio of the carbon material, KMnO4, reducing agent, potassium salt and deionized water is 0.24:0.16:(1.60-3.28):(0.008-0.12):20.
[0014] A further technical solution is that the specific process of microwave-assisted hydrothermal in-situ growth of manganese dioxide nanowires in step S3 is to place material b in a microwave hydrothermal synthesizer, with a microwave power of 500 to 3000 W, a microwave frequency of 2450 ± 50 or 915 ± 50 MHz, a reaction temperature of 180 to 200 ° C, and a reaction time of 30 to 180 min.
[0015] A further technical solution is that in step S3, the drying is performed using a household microwave oven, the microwave power is 180 to 900 W, the microwave frequency is 2450 ± 50 MHz, and the drying time is 10 to 60 s.
[0016] A further technical solution is that the specific process of the microwave tube furnace flash heating oxidation in step S4 is to irradiate at a power of 500-6000W, a microwave frequency of 2450±50 or 915±50MHz, a microwave oxidation roasting temperature of 200-800°C, a roasting time of 8-12s, and an atmosphere of air or oxygen.
[0017] A further technical solution is to prepare a magnetic manganese dioxide tunable electromagnetic wave absorbing material according to the above preparation method, which is applied in the field of electromagnetic wave absorption and shielding.
[0018] Reaction mechanism:
[0019] Preparation of manganese oxide nanowires:
[0020] 4KMnO4+2H2O→4MnO2+4KOH+3O2 (1)
[0021] 4KMnO4+2CH4N2O→2K2CO3+4MnO2+2NH3+2NO2+H2 (2)
[0022] 4MnO2+2H2O→4MnO(OH)+O2 (3)
[0023] 4MnO(OH)+O2→4MnO2+2H2O (4)
[0024] CH4N2O+H2O→NH2COO - +NH4 + (5)
[0025] 3MnO(OH)+2NH2COO - +3NH4 + →Mn3O4+5NH3+2H2O+2CO2 (6)
[0026] Firstly, the carbon material is fully stirred and mixed with a solution prepared with potassium permanganate, a reducing agent and potassium salt, and the mixture is placed in a Teflon crucible for microwave-assisted hydrothermal treatment. Potassium permanganate generates manganese dioxide under the reduction of urea, and a large number of nanowires are in situ grown on the surface of the carbon material under the guidance of potassium ions to cover it. Water molecules not only accelerate the reduction of potassium permanganate, but also convert part of the manganese dioxide into manganese oxyhydroxide. After the microwave hydrothermal synthesis, a composite containing manganese dioxide nanowires and manganese oxyhydroxide is obtained.
[0027] After washing and drying the hydrothermal product, it is placed in a microwave tube furnace for flash heating oxidation. Microwave heating adjusts manganese dioxide / manganese oxyhydroxide / manganese tetraoxide to achieve phase homogeneity regulation to coordinate the absorption and shielding of electromagnetic waves. Under microwave irradiation, manganese oxyhydroxide will be rapidly oxidized and dehydrated to manganese dioxide, and the generated water molecules will quickly escape to obtain a homogeneous manganese dioxide nanowire and carbon material composite material. The microwave flash heating of the hydrothermal product makes the product a single product of manganese dioxide, so that the manganese dioxide nanowire / carbon-based composite material finally obtained achieves the best electromagnetic wave absorption and shielding performance.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention adopts microwave hydrothermal-flash oxidation method, first obtains manganese dioxide-manganese oxyhydroxide nanowire / multilayer expanded graphite carbon-based composite material, realizes morphology modification of in-situ growth of manganese dioxide nanowire on the surface of carbon material in the hydrothermal stage, and then adjusts the physical phase composition by microwave flash oxidation to realize phase homogenization transformation, thereby strengthening its magnetic properties and realizing the dual-effect function of electromagnetic wave absorption and shielding. It overcomes the shortcomings of complicated steps, time-consuming, low efficiency and the like in the traditional process of preparing high-efficiency wave absorbing / shielding composite materials, realizes the tunability of the physical phase and electromagnetic absorption and shielding performance of manganese dioxide nanowire / carbon material composite materials, and the morphology modification of composite materials, and the preparation process is simple, efficient and easy to industrialize. The prepared cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material has a reflection loss of -40.55 to -72.29 dB at a thickness of 1.4 to 4.0 mm, and an effective absorption bandwidth of 2.2 to 4.14 GHz. After being made into a 0.1 mm film, it has a strong electromagnetic wave shielding capability of up to 117 dB at 8 to 16 GHz. It has both thin and light characteristics and excellent electromagnetic wave absorption and shielding properties. It has excellent performance in the field of electromagnetic wave absorption and shielding and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The XRD diagram of the microwave hydrothermal synthesis of cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material precursor in Example 1 and Example 2;
[0031] Figure 2 The XRD diagram of the cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material in Example 2 and Example 3;
[0032] Figure 3 is the XED image of the cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material in Example 3;
[0033] Figure 4This is a SEM image of the cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material in Example 3;
[0034] Figure 5 This is the EDS spectrum of the cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material in Example 3;
[0035] Figure 6 This is a graph showing the electromagnetic wave absorption performance of the cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material in Example 3;
[0036] Figure 7 2 is the XRD diagram of the composite material in Example 3 and Comparative Example 2. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0038] Example 1
[0039] The raw materials were weighed according to the amounts of expanded graphite 0.24 g, KMnO4 0.16 g, urea 3.28 g, KCl 0.02 g, and deionized water 20 g.
[0040] (1) First, add 20 g of deionized water into a beaker, then add KMnO4, urea, and KCl into the beaker in sequence and stir thoroughly to dissolve for 15 minutes.
[0041] (2) Add 0.24 g of expanded graphite to the mixed solution and stir thoroughly for 15 minutes.
[0042] (3) The material was placed in a Teflon beaker and transferred to a microwave hydrothermal synthesizer. The reaction temperature was 180°C, the microwave power was 1200 W, the microwave frequency was 2450±50 MHz, the heating rate was 10°C / min, and the insulation time was 60 min.
[0043] (4) Take out the material and wash it repeatedly with deionized water to remove K + ions, washing, filtering and drying the solid product to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material precursor. The drying is carried out using a household microwave oven with a microwave power of 300 W, a microwave frequency of 2450 ± 50 MHz, and a drying time of 30 s to obtain a precursor material and study its characteristics.
[0044] (5) The dried precursor was transferred to a microwave tube furnace for reaction in an air atmosphere at a reaction temperature of 200° C., a microwave power of 1400 W, a microwave frequency of 2450±50 MHz, and a holding time of 10 s.
[0045] (6) After the reaction is completed, the material is taken out to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material.
[0046] Example 2
[0047] The raw materials were weighed according to the amounts of expanded graphite 0.24 g, KMnO4 0.16 g, urea 3.28 g, KCl 0.02 g, and deionized water 20 g.
[0048] (1) First, add 20 g of deionized water into a beaker, then add KMnO4, urea, and KCl into the beaker in sequence and stir thoroughly to dissolve for 15 minutes.
[0049] (2) Add 0.24 g of expanded graphite to the mixed solution and stir thoroughly for 15 minutes.
[0050] (3) The material was placed in a Teflon beaker and transferred to a microwave hydrothermal synthesizer. The reaction temperature was 180°C, the microwave power was 1200 W, the microwave frequency was 2450±50 MHz, the heating rate was 10°C / min, and the insulation time was 120 min.
[0051] (4) Take out the material and wash it repeatedly with deionized water to remove K + ions, washing, filtering and drying the solid product to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material precursor. The drying is carried out using a household microwave oven with a microwave power of 300 W, a microwave frequency of 2450±50 MHz and a drying time of 30 s.
[0052] (5) The dried precursor was transferred to a microwave tube furnace for reaction in an air atmosphere at a reaction temperature of 200° C., a microwave power of 1400 W, a microwave frequency of 2450±50 MHz, and a holding time of 10 s.
[0053] (6) After the reaction is completed, the material is taken out to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material.
[0054] Example 3
[0055] The raw materials were weighed according to the amounts of expanded graphite 0.24 g, KMnO4 0.16 g, urea 3.28 g, KCl 0.02 g, and deionized water 20 g.
[0056] (1) First, add 20 g of deionized water into a beaker, then add KMnO4, urea, and KCl into the beaker in sequence and stir thoroughly to dissolve for 15 minutes.
[0057] (2) Add 0.24 g of expanded graphite to the mixed solution and stir thoroughly for 15 minutes.
[0058] (3) The material was placed in a Teflon beaker and transferred to a microwave hydrothermal synthesizer. The reaction temperature was 180°C, the microwave power was 1200 W, the microwave frequency was 2450±50 MHz, the heating rate was 10°C / min, and the insulation time was 120 min.
[0059] (4) Take out the material and wash it repeatedly with deionized water to remove K + ions, washing, filtering and drying the solid product to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material precursor. The drying is carried out using a household microwave oven with a microwave power of 300 W, a microwave frequency of 2450±50 MHz and a drying time of 30 s.
[0060] (5) The dried precursor was transferred to a microwave tube furnace for reaction under air atmosphere at a reaction temperature of 400° C., a microwave power of 3000 W, a microwave frequency of 2450±50 MHz, and a holding time of 10 s.
[0061] (6) After the reaction is completed, the material is taken out to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material.
[0062] The XRD patterns of the cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite precursor obtained by microwave hydrothermal treatment are shown in Figure 2. Figure 1 As shown in Figure 2, the crystallinity of the prepared cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material is significantly improved under 120 min microwave hydrothermal time compared to 60 min. Figure 2 As shown by Figure 2 It can be seen that the prepared cage-like manganese dioxide nanowires all maintain the characteristic diffraction peaks of the manganese oxide phase. And the higher the temperature, the more obvious the characteristic diffraction peaks of the manganese oxide phase. It can be seen that the method can be used to quickly and efficiently synthesize and prepare a homogenized manganese dioxide phase, and the microwave radiation oxidation has a significant effect on the adjustment strategy of the transformation of manganese oxide hydroxide to manganese dioxide phase, achieving a dual synergistic effect of electromagnetic wave absorption and shielding.
[0063] The XED results of the cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material prepared in Example 3 are as follows: Figure 3 As shown, the prepared composite material maintains the original phase of expanded graphite and exhibits the characteristic diffraction peaks of manganese dioxide. The SEM electron microscope image and EDS energy spectrum of the cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material prepared in Example 3 are respectively Figure 4 , Figure 5 .from Figure 4 It can be seen that the morphology of expanded graphite is modified during the reaction process, and manganese dioxide nanowires grow on the surface of the material to form a cage-like multilayer three-dimensional structure; at the same time, Figure 5EDS energy spectrum analysis found that no new elements appeared. It can be seen that the present method can be used to modify the surface of expanded graphite while realizing the in-situ growth synthesis of manganese dioxide nanowires, shortening the preparation steps of the composite material, being simple and efficient, and easy for industrial application.
[0064] The cage-like manganese dioxide nanowire multilayer expanded graphite composite material obtained in Example 3 was used to prepare a coaxial ring and tested in the range of 1-18 GHz. The prepared absorbing material had a RLmin of -75.56 dB and an EAB of 3.87 GHz for 15.16 GHz electromagnetic waves at a matching thickness of 1.48 mm. Figure 6 The cage-like manganese dioxide nanowire multilayer expanded graphite composite material was pressed into a 0.1mm film at 20MPa and tested in the range of 12-19GHz. It has a strong electromagnetic wave shielding ability of 117dB in the X and P bands, and has excellent electromagnetic wave absorption and shielding properties. It has excellent performance and application prospects in the fields of electromagnetic protection and stealth materials.
[0065] Example 4
[0066] The raw materials were weighed according to the amounts of expanded graphite 0.24 g, KMnO4 0.16 g, hydrazine hydrate 1.60 g, KCl 0.02 g, and deionized water 20 g.
[0067] (1) First, add 20g of deionized water into a beaker, then add KMnO4, hydrazine hydrate, and KCl into the beaker in sequence and stir thoroughly to dissolve for 15 minutes.
[0068] (2) Add 0.24 g of expanded graphite to the mixed solution and stir thoroughly for 15 minutes.
[0069] (3) The material was placed in a Teflon beaker and transferred to a microwave hydrothermal synthesizer. The reaction temperature was 180°C, the microwave power was 1200 W, the microwave frequency was 2450±50 MHz, the heating rate was 10°C / min, and the insulation time was 120 min.
[0070] (4) Take out the material and wash it repeatedly with deionized water to remove K + ions, washing, filtering and drying the solid product to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material precursor. The drying is carried out using a household microwave oven with a microwave power of 300 W, a microwave frequency of 2450±50 MHz and a drying time of 30 s.
[0071] (5) The dried precursor was transferred to a microwave tube furnace for reaction under air atmosphere at a reaction temperature of 400° C., a microwave power of 3000 W, a microwave frequency of 2450±50 MHz, and a holding time of 10 s.
[0072] (6) After the reaction is completed, the material is taken out to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material.
[0073] Example 5
[0074] The raw materials were weighed according to the amounts of expanded graphite 0.24 g, KMnO4 0.16 g, urea 3.28 g, KNO3 0.008 g, and deionized water 20 g.
[0075] (1) First, add 20g of deionized water into a beaker, then add KMnO4, urea, and KNO3 into the beaker in sequence and stir thoroughly to dissolve for 15 minutes.
[0076] (2) Add 0.24 g of expanded graphite to the mixed solution and stir thoroughly for 15 minutes.
[0077] (3) The material was placed in a Teflon beaker and transferred to a microwave hydrothermal synthesizer. The reaction temperature was 180°C, the microwave power was 1200 W, the microwave frequency was 2450±50 MHz, the heating rate was 10°C / min, and the insulation time was 120 min.
[0078] (4) Take out the material and wash it repeatedly with deionized water to remove K + ions, washing, filtering and drying the solid product to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material precursor. The drying is carried out using a household microwave oven with a microwave power of 300 W, a microwave frequency of 2450±50 MHz and a drying time of 30 s.
[0079] (5) The dried precursor was transferred to a microwave tube furnace for reaction under air atmosphere at a reaction temperature of 400° C., a microwave power of 3000 W, a microwave frequency of 2450±50 MHz, and a holding time of 10 s.
[0080] (6) After the reaction is completed, the material is taken out to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material.
[0081] Example 6
[0082] The raw materials were weighed according to the amounts of expanded graphite 0.24 g, KMnO4 0.16 g, urea 3.28 g, K2SO4 0.12 g, and deionized water 20 g.
[0083] (1) First, add 20g of deionized water into a beaker, then add KMnO4, urea, and K2SO4 into the beaker in sequence and stir thoroughly to dissolve for 15 minutes.
[0084] (2) Add 0.24 g of expanded graphite to the mixed solution and stir thoroughly for 15 minutes.
[0085] (3) The material was placed in a Teflon beaker and transferred to a microwave hydrothermal synthesizer. The reaction temperature was 180°C, the microwave power was 1200 W, the microwave frequency was 2450±50 MHz, the heating rate was 10°C / min, and the insulation time was 120 min.
[0086] (4) Take out the material and wash it repeatedly with deionized water to remove K + ions, washing, filtering and drying the solid product to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material precursor. The drying is carried out using a household microwave oven with a microwave power of 300 W, a microwave frequency of 2450±50 MHz and a drying time of 30 s.
[0087] (5) The dried precursor was transferred to a microwave tube furnace for reaction under air atmosphere at a reaction temperature of 400° C., a microwave power of 3000 W, a microwave frequency of 2450±50 MHz, and a holding time of 10 s.
[0088] (6) After the reaction is completed, the material is taken out to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material.
[0089] Comparative Example 1
[0090] The raw materials were weighed according to the amounts of expanded graphite 0.24 g, KMnO4 0.16 g, urea 3.28 g, KCl 0.02 g, and deionized water 20 g.
[0091] (1) First, add 20 g of deionized water into a beaker, then add KMnO4, urea, and KCl into the beaker in sequence and stir thoroughly to dissolve for 15 minutes.
[0092] (2) Add 0.24 g of expanded graphite to the mixed solution and stir thoroughly for 15 minutes.
[0093] (3) The material was placed in a hydrothermal reactor and transferred to a conventional hydrothermal synthesis reaction equipment for testing. The reaction temperature was 180°C and the insulation time was 24 h.
[0094] (4) Take out the material, wash it repeatedly with deionized water, take out the solid product and dry it. Drying is carried out using a household microwave oven with a microwave power of 300 W, a microwave frequency of 2450 ± 50 MHz, and a drying time of 30 s.
[0095] Comparing Comparative Example 1 with Example 1, it can be seen that microwave hydrothermal treatment greatly shortens the reaction time compared with conventional hydrothermal treatment.
[0096] Comparative Example 2
[0097] The raw materials were weighed according to the amounts of expanded graphite 0.24 g, KMnO4 0.16 g, urea 3.28 g, KCl 0.02 g, and deionized water 20 g.
[0098] (1) First, add 20 g of deionized water into a beaker, then add KMnO4, urea, and KCl into the beaker in sequence and stir thoroughly to dissolve for 15 minutes.
[0099] (2) Add 0.24 g of expanded graphite to the mixed solution and stir thoroughly for 15 minutes.
[0100] (3) The material was placed in a Teflon beaker and transferred to a microwave hydrothermal synthesizer. The reaction temperature was 180°C, the microwave power was 1200 W, the microwave frequency was 2450±50 MHz, the heating rate was 10°C / min, and the insulation time was 120 min.
[0101] (4) Take out the material and wash it repeatedly with deionized water to remove K + ions, washing, filtering and drying the solid product to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material precursor. The drying is carried out using a household microwave oven with a microwave power of 300 W, a microwave frequency of 2450±50 MHz and a drying time of 30 s.
[0102] (5) The dried precursor was transferred to a muffle furnace for reaction in an air atmosphere at a reaction temperature of 400°C, a heating rate of 10°C / min, and a holding time of 40 min.
[0103] (6) After the reaction is completed, the material is taken out to obtain a composite material.
[0104] XRD comparison of the composite materials of Example 3 and Comparative Example 2 Figure 7 As shown, microwave oxidation roasting not only greatly reduces the time, but also promotes the homogenization of the manganese dioxide phase. While microwaves are highly efficient and energy-saving, they also achieve a better microstructure, obtaining a homogeneous single material with efficient electromagnetic wave absorption.
[0105] Although the present invention is described herein with reference to a number of illustrative embodiments of the present invention, it will be appreciated that those skilled in the art may devise numerous other modifications and implementations that fall within the scope of the present disclosure. More specifically, within the scope of the present disclosure, drawings, and claims, a variety of variations and modifications may be made to the components or layout. In addition to variations and modifications to the components or layout, other uses will be apparent to those skilled in the art.
Claims
1. A method for preparing a magnetic manganese dioxide tunable electromagnetic wave absorbing material, characterized in that The steps include: S1. Weigh KMnO4, a reducing agent and potassium salt in turn and add them to a beaker filled with deionized water, stir until mixed, and obtain material a; S2. Weigh the carbon material, add it to material a, stir and mix thoroughly to obtain material b; S3. Place material b in a Teflon crucible and use microwave-assisted hydrothermal in-situ growth of manganese oxide nanowires. After the reaction is completed, rinse with deionized water to remove K + ions, washed and filtered, and then dried to obtain material c, i.e., a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material precursor; S4. Place material c in a quartz crucible, perform flash heating oxidation in a microwave tube furnace, and deeply oxidize the material on its surface that has not been completely converted into manganese oxide to obtain a cage-like manganese dioxide nanowire / multilayer expanded graphite carbon-based composite material.
2. The method for preparing a magnetic manganese dioxide tunable electromagnetic wave absorbing material according to claim 1, characterized in that: The carbon material in step S2 is one or more of expanded graphite, carbon fiber, carbon nanotube, and carbon black.
3. The method for preparing a magnetic manganese dioxide tunable electromagnetic wave absorbing material according to claim 1, characterized in that: In step S1, the reducing agent is one of urea and hydrazine hydrate, and the potassium salt is one of KCl, KNO3, and K2SO4.
4. The method for preparing a magnetic manganese dioxide tunable electromagnetic wave absorbing material according to claim 1, characterized in that: The mass ratio of the carbon material, KMnO4, reducing agent, potassium salt and deionized water is 0.24:0.16:(1.60-3.28):(0.008-0.12):
20.
5. The method for preparing a magnetic manganese dioxide tunable electromagnetic wave absorbing material according to claim 1, characterized in that: The specific process of microwave-assisted hydrothermal in-situ growth of manganese dioxide nanowires in step S3 is to place material b in a microwave hydrothermal synthesizer, with a microwave power of 500 to 3000 W, a microwave frequency of 2450±50 or 915±50 MHz, a reaction temperature of 180 to 200° C., and a reaction time of 30 to 180 min.
6. The method for preparing a magnetic manganese dioxide tunable electromagnetic wave absorbing material according to claim 1, characterized in that: In step S3, the drying is performed using a household microwave oven, the microwave power is 180 to 900 W, the microwave frequency is 2450 ± 50 MHz, and the drying time is 10 to 60 s.
7. The method for preparing a magnetic manganese dioxide tunable electromagnetic wave absorbing material according to claim 1, characterized in that: The specific process of the microwave tube furnace flash heating oxidation in step S4 is to irradiate at a power of 500-6000W, a microwave frequency of 2450±50 or 915±50MHz, a microwave oxidation roasting temperature of 200-800°C, a roasting time of 8-12s, and an atmosphere of air or oxygen.
8. A magnetic manganese dioxide tunable electromagnetic wave absorbing material, characterized in that: The material is prepared according to the preparation method of a magnetic manganese dioxide tunable electromagnetic wave absorbing material according to claims 1 to 7, and is applied in the field of electromagnetic wave absorption and shielding.
Citation Information
Patent Citations
Preparation method of graphene oxide / manganese dioxide composite material
CN106698412A
Method for preparing carbon-coated manganese oxygen compound electromagnetic wave absorbing material
CN110856432A
SiC-coated MnO2-x / Mn3O4-x nano composite wave-absorbing material and preparation method thereof
CN117800341A
Metal ion-doped magnetic dielectric synergistic core-shell structure wave-absorbing material as well as preparation method and application thereof
CN118026269A
Preparation and application in wave absorption of titanium sulfide nanomaterial and composite material thereof
US20230063025A1